2017
DOI: 10.1161/circimaging.116.005585
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 18 F-Fluorodeoxyglucose Uptake Pattern in Noninfected Prosthetic Heart Valves

Abstract: Background-18 F-Fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) has been recently acknowledged as a diagnostic tool for prosthetic valve endocarditis, but its specificity is limited by uptake on noninfected valves. The objective of this study was to outline the main features of FDG uptake on PET/CT in patients with noninfected prosthetic heart valve (PHV). Methods and Results-Our institution's PET/CT database was reviewed to identify patients with PHV, excluding those suspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
5
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 23 publications
3
69
5
4
Order By: Relevance
“…However, the evaluation of prosthetic valves in PET/CT is not well defined. Noninfected prosthetic heart valves often display homogenous FDG uptake even in the absence of infection . The value of PET/CT is in cases where traditional Duke criteria can be indeterminate, such as in patients with prosthetic valves and transcatheter therapies where echocardiography may be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…However, the evaluation of prosthetic valves in PET/CT is not well defined. Noninfected prosthetic heart valves often display homogenous FDG uptake even in the absence of infection . The value of PET/CT is in cases where traditional Duke criteria can be indeterminate, such as in patients with prosthetic valves and transcatheter therapies where echocardiography may be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that non-infected prosthetic valves frequently display homogeneous 18 F-FDG uptake that may remain steady over time 17. This can be a source of false-positive results.…”
Section: Discussionmentioning
confidence: 99%
“…6 A reasonable alternative would be to agree on dedicated PET protocols for the imaging of patients with a suspicion of PVE that offer a compromise between image quality and the need for standardization of PET acquisitions, in a similar way to what has already been proposed for the imaging of atherosclerosis that present similar constraints. 7 Second, valves are subjected to important cardiac and respiratory motion. Signal quantification would certainly benefit from the development of dual cardiac and respiratory gating and motion correction of PET acquisitions.…”
Section: Standardization Of Pet Protocols In Patients With Pvementioning
confidence: 99%
“…The interpretation of PET images is the most difficult when FDG uptake is moderate in valves, because this aspect is frequently found in non-infected prosthetic valves in relation to chronic immune reactions and is hard to distinguish from active infection. 7 In this situation, additional criteria need to be taken into account such as the pattern of FDG uptake, the persistence of FDG signal on non-attenuation corrected images, the localization of the signal in relation to cardiac structures, and to morphological aspects observed on echocardiography or cardiac CTA. 10,11 In particular, the presence of focal or heterogeneous FDG signal extending outside the prosthetic contours is suggestive of infection.…”
Section: Integrating Clinical Biology and Imaging For The Diagnosticmentioning
confidence: 99%